Handle with Care - Farah, Maya F. (2020)
The purpose of this study is to evaluate consumers’ reactions toward drone delivery service. Qualitative data was collected based on comments posted following a YouTube video. A thematic inductive analysis was used in order to analyze the data based on YouTube participants’ comments. The results of this study revealed that similarly to any other forms of innovation, consumers’ expressed their resistance to this form of delivery in two forms: cognitive and affective. Taking into account that drone delivery service is still under the testing phase, this study was limited to finding sufficient and actual users who can contribute to the study with real and concrete concerns. This limitation restricts our understanding of consumers’ reactions to drone delivery service to theoretical assumptions. Commercial companies and retailers may benefit from this research to get a deeper understanding about the main consumers’ concerns and perceived risks towards the drone delivery service. Thus, this research may guide companies with ideas on how to better serve customers to increase the chances of adoption. Previous literature has largely explored the concept of technological innovations. However, no research to date has studied consumers’ reactions towards this new form of delivery service.